Angiotensin-(1-9) ameliorates pulmonary arterial hypertension via angiotensin type II receptor - Cha, Seung Ah (Korean J Physiol Pharmacol, 2018)
Angiotensin-(1-9) [Ang-(1-9)], generated from Ang I by Ang II converting enzyme 2, has been reported to have protective effects on cardiac and vascular remodeling. However, there is no report about the effect of Ang-(1-9) on pulmonary hypertension. The aim of the present study is to investigate whether Ang-(1-9) improves pulmonary vascular remodeling in monocrotaline (MCT)-induced pulmonary hypertensive rats. Sprague-Dawley rats received Ang-(1-9) (576 µg/kg/day) or saline via osmotic mini-pumps for 3 weeks. Three days after implantation of osmotic mini-pumps, 50 mg/kg MCT or vehicle were subcutaneously injected. MCT caused increases in right ventricular weight and systolic pressure, which were reduced by co-administration of Ang-(1-9). Ang-(1-9) also attenuated endothelial damage and medial hypertrophy of pulmonary arterioles as well as pulmonary fibrosis induced by MCT. The protective effects of Ang-(1-9) against pulmonary hypertension were inhibited by Ang type 2 receptor (AT(2)R) blocker, but not by Mas receptor blocker. Additionally, the levels of LDH and inflammatory cytokines, such as TNF-α, MCP-1, IL-1β, and IL-6, in plasma were lower in Ang-(1-9) co-treated MCT group than in vehicle-treated MCT group. Changes in expressions of apoptosis-related proteins such as Bax, Bcl-2, Caspase-3 and -9 in the lung tissue of MCT rats were attenuated by the treatment with Ang-(1-9). These results indicate that Ang-(1-9) improves MCT-induced pulmonary hypertension by decreasing apoptosis and inflammatory reaction via AT(2)R.